The effect of brand personality and brand identification on customer retention : examining Islamic banking services in Malaysia / Husniyati Ali, 'Ismah Osman and Sharifah Faigah Syed Alwi - Ali, Husniyati; Osman, 'Ismah; Syed Alwi, Sharifah Faigah (Research Management Institute (RMI), 2011)
The development of Islamic banks in Malaysia is increasingly challenging with more banks offering products and services based on Islamic principles. Hence, this study explores customers' perception towards corporate image and its impact on selfexpressive value, brand distinctiveness, brand attractiveness as well as brand identification towards their most preferred Islamic bank in Malaysia. Institutional theory as well as theory of social identification was exploited as the theoretical foundation for developing the conceptual model. Accordingly, data was collected firstly, through an exploratory study, through interviews with customers, Shari' ah supervisors, practitioners and lecturers in Islamic banking. Next, 'self-administered questionnaires were distributed among 600 customers of Islamic banks in Kuala Lumpur through purposive sampling, specifically in selected Islamic banks, shopping malls and stations of public transportation. Analysis of data was conducted through descriptive, exploratory and confirmatory factor analysis. Subsequently, structural equation modelling with 308 respondents was then conducted to test the hypothesized relationships among the constructs, as postulated in the model. Nine hypothesis links were supported, while eight were rejected. Results indicate that firstly, corporate image of Islamic banks are determined by institutional image and performative image. Performative image constitutes items including friendliness, reliability, honesty, security, achievement-orientation, leading-orientation, up-to-date and excitement. In consequence, institutional image constitutes god-consciousness, which includes items like being Islamic, humbleness, fairness and trustworthiness. Secondly, institutional image and performative image have impact on brand attractiveness. However, they do not have an impact on self-expressive value, brand distinctiveness and brand identification. Thirdly, self-expressive value has an impact on brand's attractiveness. Fourth, brand's attractiveness and brand's distinctiveness have an impact on consumers' identification with a brand. Fifth, brand's attractiveness has an impact on word of mouth, as well as brand loyalty. Sixth, consumers' identification with a brand has an impact on brand loyalty. It is hoped that this study would facilitate in developing corporate image in Islamic banks, due to intense competition from many players of the industry.